Synthesis of acyclic nucleoside phosphonates targeting flavin-dependent thymidylate synthase in Mycobacterium tuberculosis. (15th September 2021) - Biteau, Nicolas G.; Roy, Vincent; Lambry, Jean-Christophe; Becker, Hubert F.; Myllykallio, Hannu; Agrofoglio, Luigi A.
Graphical abstract: Abstract: Flavin-Dependent Thymidylate Synthase ( FDTS ) encoded by ThyX gene was discovered as a new class of thymidylate synthase involved in the de novo synthesis of dTMP named only in 30 % of human pathogenic bacteria. This target was pursed for the development of new antibacterial agents against multiresistant pathogens. We have developed a new class of ANPs based on the mimic of two natural's cofactors (dUMP and FAD) as inhibitors against Mycobacterium tuberculosis ThyX . Several synthetic efforts were performed to optimize regioselective N1-alkylation, cross-coupling metathesis and Sonogashira cross-coupling. Compound 19c showed a poor 31.8% inhibitory effect on ThyX at 200 μM.